READER’S INTERPRETATION ON SOCIAL CRITICISM TOWARD SOEHARTO FOUND IN TRUCK GRAFFITI - MELIANA, IKE (Jurnal Ilmiah Mahasiswa FIB, 2014)
Meliana, Ike. 2014. Reader’s Interpretation on Social criticism toward Soeharto Found In Truck Graffiti. Study Program of English. Universitas Brawijaya. Supervisor: NurulChojimah. Co- Supervisor: EniMaharsiKeywords: CDA, Social Criticism, Graffiti This research is about analysis of Social Criticism toward Soeharto Found in Truck Graffiti. The aims are to explain about the hidden meaning of the truck graffiti and also to explain how the difference between female and male readers in interpreting that truck graffiti.This research uses qualitative research approach,in the form of documentanalysis. Research results the same understanding that the meaning of criticism in the truck graffiti is about the former president greets his citizen and it seems like criticizing the ruling government. In this research is found that male readers are more critical in interpreting this kind of graffiti than female readers.In this research also provides the result based on the analysis of syntagmatic perspective that the graffiti“Piye kabare? Enak’anjamanku to le?” is communicative, it provokes the readers mind to compare the reign of Soeharto and the ruling government but it softens its way of provoking and comparing while graffiti “Isehpenakzamanku” reveals the sense of arrogant on it because it directly states its admission. And then from paradigmatic perspective, both versions of the graffiti is better than any other version of the graffiti which express the same idea.After conducting this research, in fact the research respondents interest in such truck graffiti because the idea on it, and it iskind of creativity in expressing idea, protest, etc.The writer suggests that the application of Critical Discourse Analysis shouldbe given more time in practice, so it will be easier for the next researcher to analyze using this theory. And then the writer also expects that the next researcher can explore deeper and wider about the topic of this Critical Discourse Analysis.